The Role of Educational Planning in SDG Implementation - Kurniatun, Taufani Chusnul (Pedagogi: Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the strategic role of educational planning in supporting the implementation of the Sustainable Development Goals (SDGs), particularly the fourth goal on quality education (SDG 4). Using a literature review method, this study integrates findings from various international and national studies over the past five years that highlight the relationship between education policy, sustainable development governance, and the effectiveness of data-driven and participatory planning. The analysis shows that educational planning plays a crucial role not only as an administrative tool but also as an instrument of social transformation that directs policies, resources, and programs toward achieving the SDGs. Implementation in Indonesia has been integrated into the National Medium-Term Development Plan (RPJMN) and regional development plans, but its effectiveness is still influenced by regional disparities, institutional capacity, and limited human resources. Recent studies confirm that the success of educational planning in supporting SDG 4 depends heavily on systematic, participatory, data-driven, and cross-sectoral planning mechanisms that synergize education with other sectors such as health, employment, and technology. Thus, inclusive and adaptive educational planning is the foundation for realizing quality education and achieving sustainable development goals in Indonesia.